1993
DOI: 10.1152/ajpregu.1993.265.2.r348
|View full text |Cite
|
Sign up to set email alerts
|

GABA stimulation of gonadotropin-II release in goldfish: involvement of GABAA receptors, dopamine, and sex steroids

Abstract: The involvement of gamma-aminobutyric acid (GABA) in regulation of pituitary gonadotropin-II (GTH-II) release was studied in the goldfish. Intraperitoneal injection of GABA (300 micrograms/g) stimulated an increase in serum GTH-II levels at 30 min postinjection. The GABAA receptor agonist muscimol (0.1-10 micrograms/g) stimulated GTH-II in a dose-dependent manner. Baclofen, a GABAB receptor agonist, had a small but significant stimulatory effect at 1 and 10 micrograms/g; the amount of GTH-II released in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 0 publications
2
54
0
3
Order By: Relevance
“…However, a rôle for GABA on GTH2 sécrétion was clearly demonstrated in goldfish. Indeed, intraperitoneal or intracerebroventricular injections of GABA or GABA-transaminase inhibitors stimulate GTH2 release (KAH et al, 1992 ;TRUDEAU et al, 1993a). Since a direct action on GTH cell has not been demonstrated in vitro, it has been postulated that the stimulatory actions of GABA on GTH2 release are mediated via GnRH and/or dopaminergic Systems.…”
Section: Which Other Potential Target ?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a rôle for GABA on GTH2 sécrétion was clearly demonstrated in goldfish. Indeed, intraperitoneal or intracerebroventricular injections of GABA or GABA-transaminase inhibitors stimulate GTH2 release (KAH et al, 1992 ;TRUDEAU et al, 1993a). Since a direct action on GTH cell has not been demonstrated in vitro, it has been postulated that the stimulatory actions of GABA on GTH2 release are mediated via GnRH and/or dopaminergic Systems.…”
Section: Which Other Potential Target ?mentioning
confidence: 99%
“…Since a direct action on GTH cell has not been demonstrated in vitro, it has been postulated that the stimulatory actions of GABA on GTH2 release are mediated via GnRH and/or dopaminergic Systems. The stimulatory effects of GABA on GTH2 release in goldfish resuit from both increased GnRH release and decreased dopaminergic activity (TRUDEAU et al, 1993a). In addition, several in vivo experiments have shown that GABA stimulâtes GTH2 sécrétion in fish at early stages of gonadal development but was ineffective in mature or sexually regressed goldfish, suggesting that the stimulating effects of GABA on GTH2 levels dépend on the steroid environment (KAH et al, 1992).…”
Section: Which Other Potential Target ?mentioning
confidence: 99%
“…However, a significant stimulatory role for GABA in the control of hypothalamic GnRH (GnRH) (6) and pituitary gonadotropic hormone (7,8) release is now apparent. Our work using the adult goldfish model (reviewed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, pharmacological evidence indicates that GABA action to enhance GTH-II release is mediated by dual stimulatory effects on GABA A and GABA B receptors (8), which may explain why GABA has a dominant stimulatory effect in the goldfish model. GABA acts to stimulate GTH-II release by enhancement of GnRH release from the nerve terminal within the goldfish pituitary and also by inhibition of the inhibitory preoptic-hypothalamic dopaminergic system.…”
mentioning
confidence: 99%
See 1 more Smart Citation